KETERKAITAN IMPLEMENTASI ANGGARAN BERBASIS KINERJA DENGAN AKUNTABILITAS PROGRAM PRIORITAS NASIONAL KEMENTERIAN AGRARIA DAN TATA RUANG/ BADAN PERTANAHAN NASIONAL - Suwarni -; Siti Nuraini (Governance, 2021)
National Priority Program policy Complete Systematic Land Registration (PTSL) in the Ministry of Agrarian and Spatial Planning / National Land Agency as an effort to realize good governance in order to accelerate the provision of legal certainty over land rights carried out in 2017-2024. The Bandung City Land Office as the implementing work unit is the only Land Office that has completed PTSL in 2017 with 152% achievement, while the August 2017 research with the results of the achievement is only 7.78% target, so that the implementation of performance-based budgeting needs to be linked with accountability. The results showed that the implementation of the implementation of performance-based budgeting at the Bandung City Land Office had implemented budget principles based on input, output and outcome with monitoring and evaluation supported by the application of the Land Program Quality Control System (SKMPP) so that it was effective and efficient. Financial accountability and performance accountability have been integrated into the Command Agency Performance Accountability System (SAKIP). The linkage between the implementation of performance-based budgets greatly influences the accountability of national priority programs. The researcher suggested to the Ministry of Agrarian and Spatial Planning / National Land Agency to make planning more optimally and the preparation of standard costs should involve work units that represent regional characteristics and conditions so that the unit of budget allocation costs in achieving performance as needed.